2010
DOI: 10.1177/009102601003900403
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Clerks: Examining a Model of Job Satisfaction

Abstract: Using data from a survey of municipal clerks in the state of Illinois, this research tests a model of job satisfaction for municipal employees based on previous research by Ellickson and Logsdon. Our hypothesis is that the model will not hold true for this sub-group of municipal employees because municipal clerks are different from other public sector employees. Clerks are different in part because their job duties and responsibilities are set out by statute, there is a great deal of autonomy, and the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The survey questions are presented in the appendix. The use of the survey instrument in previous studies of Illinois and Kentucky municipal clerks (Gordon, 2007, October;Gordon, 2007, November;Gordon, 2008, January;Gordon, 2008, February;Gordon et al, 2010) supports the reliability and validity of the survey instrument and specific questions. In June 2008, 1,000 surveys were mailed via the United States Postal Service to a random sample of the IIMC membership mailing list.…”
Section: The Surveymentioning
confidence: 59%
See 2 more Smart Citations
“…The survey questions are presented in the appendix. The use of the survey instrument in previous studies of Illinois and Kentucky municipal clerks (Gordon, 2007, October;Gordon, 2007, November;Gordon, 2008, January;Gordon, 2008, February;Gordon et al, 2010) supports the reliability and validity of the survey instrument and specific questions. In June 2008, 1,000 surveys were mailed via the United States Postal Service to a random sample of the IIMC membership mailing list.…”
Section: The Surveymentioning
confidence: 59%
“…Survey questions were developed and extended primarily from the work of Blackburn and Bruce (1989), Ellickson and Logsdon (2001), and Gordon et al (2010) to measure the perceptions of clerks regarding variables identified in the literature as related to job satisfaction. The survey questions are presented in the appendix.…”
Section: The Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Pengawasan didefinisikan sebagai pengawasan yang dilakukan oleh supervisor untuk membantu karyawan bekerja atau memberikan arahan ketika karyawan tidak memahami konteks yang harus dikerjakan [10] J. Kerjasama Tim Kerjasama tim didefinisikan sebagai langkah untuk meningkatkan motivasi, otonomi karyawan, pengaruh, dan pembentukan ikatan yang kuat dengan anggota lainnya [8].…”
Section: Pengawasanunclassified
“…For instance: various aspects of job satisfaction in health-care organizations and factors contributing to a relatively low level of job satisfaction of medical teachers (Bhatnagar and Srivastava, 2012;2013); factors affecting employees' job satisfaction in public hospitals (Miryala and Thangella, 2012;2013 andRad andDe Moraes, 2009); factors influencing job satisfaction amongst doctors in corporate and private hospitals (Miryala and Thangella, 2012;2013); relationships among internal marketing perceptions, organizational support, job satisfaction and role behavior in healthcare organizations (Yang, 2010), determinants of job satisfaction and intentions to quit of offshore workers in the UK North Sea oil and gas industry (Dickey et al 2011), job satisfaction of university teachers (Sharma and Jyoti, 2009); job satisfaction of municipal clerks (Gordon et al 2010); job satisfaction of knowledge workers (Bakotic, 2012); role of stress and locus of control in job satisfaction among middle managers (Singh and Ashish, 2011); organizational learning capability and job satisfaction in the ceramic tile industry (Chiva and Alegre, 2009); relationship between college quality, earnings, and job satisfaction among recent college graduates (Liu et al 2010); ministry clergy burnout and job satisfaction (Miner et al 2010); job satisfaction in the public service (Taylor and Westover, 2011); relationships among transformational leadership, job satisfaction, commitment foci and commitment bases in the public sector (Yang et al 2011b, p.265-278); impact of management reform on employee job satisfaction in federal agencies (Yang and Kassekert, 2010); job satisfaction in the home health care context (Morgan et al 2010); and even individual and environmental factors related to job satisfaction in people with severe mental illness employed in social enterprises (Villotti, 2012).…”
mentioning
confidence: 99%